Exploring the Professional Responsibility Concern Process: An Alberta Perspective. Issue 2 (April 2020) - Raymond, Christy; Toloiy, Raechelle; Bergman, Joshua
Abstract : Background: Registered nurses are pivotal in the analysis, recognition, and reporting of patient safety issues before harm occurs to patients. Little has been written about the relationship between the professional responsibility of reporting safety concerns and the processes that exist. Problem: More needs to be known about how nurses can best report factors in work environments that impact patient safety. Learning more about processes that exist amidst literature that illuminates the issues related to reporting and patient safety culture is needed. Also, best practice or key exemplars depicting how professional responsibility has been implemented are needed. Limited has been written exploring professional responsibility concern processes in Canada and internationally. Approach: We completed a case study exploration comprising a public facing Web site scan of information about professional responsibility-like processes across Canada, as well as an extensive literature search exploring factors that are linked with nurse reporting of patient safety concerns. Conclusion: Themes from related literature identify patient safety culture, leadership qualities, communication, positive nurse factors, speaking up, and whistle-blowing as important aspects that facilitate, or are related to, the ability for nurses to express professional responsibility concerns. Alberta has a well-developed system of reporting such concerns; however, the lack of research and literature on these topics requires additional focus in nursing internationally. Abstract : Supplemental Digital Content is Available in the Text.